Childhood maltreatment and aggression: The mediating roles of hostile attribution bias and anger rumination. (1st August 2020) - Zhu, Wenfeng; Chen, Yunli; Xia, Ling-Xiang
Abstract: Childhood maltreatment is a recognized risk factor for aggressive behaviours. Although some mediators were found, the mental mechanism underlying the effect of childhood maltreatment on aggression seems to remains unclear. In the present study, a temporal path model (represented by hostile attribution bias (HAB) and anger rumination) was developed to explain the mediating mechanism in the relationship between childhood maltreatment and aggression. The Childhood Trauma Questionnaire, Word-Sentence Association Paradigm-Hostile, Anger Rumination Scale, and Buss-Perry Aggression Questionnaire were used in a sample of 973 undergraduate students. Multiple mediation analysis and bootstrapping were conducted via Mplus7 to assess whether HAB and anger rumination mediated the association between childhood maltreatment and aggression. The results showed HAB (indirect effects = 0.04, 95% confidence intervals [0.03 0.06]) and anger rumination (indirect effects = 0.10, 95% confidence intervals [0.08 0.13]) mediated the link between child maltreatment and aggressive behaviours. Pairwise contrast to the indirect effect indicated that anger rumination had a stronger mediating effect than HAB ( p   < 0.001 ). We argue that child maltreatment may trigger immediate aggression during a provoking event through HAB (an in-process mechanism) and lead to delayed aggression after interpersonal conflict through anger rumination (a post-process mechanism).